To Determine the Incidence of Di?cult Intubation - Garg, Ruchi; Tajne, Narendra; Neeraj (Academia Anesthesiologica International, 2020)
Introduction: To determine the incidence of difficult intubation among patients scheduled for surgery under general anesthesia. Subjects and Methods: Prospective Observational study conducted on 410 patients. Anesthesia induced & laryngoscopy performed. Difficulty in intubation graded according to Intubation Difficulty Scale (IDS). Results: Based on IDS score, the incidence of difficult intubation found to be 22.5%. A slight difficulty in 22% (IDS = 1-5) & moderate to major difficulty (IDS >5) in 0.5% cases. Intubation done successfully in all patients. Conclusion: The incidence of difficult intubation among patients scheduled for surgery under general anesthesia observed to be 22.5%